Microstructural evolution characterization of Fe-Nb-B ternary systems processed by ball milling - Ipus, J; Blázquez, J; Conde, A; Lozano-Perez, S (2009)
Fe-Nb-B alloys prepared by ball milling can undergo a complex microstructural evolution during milling. In order to overcome the limitations imposed by traditional X-ray bulk analysis, a comprehensive multi-technique approach was devised to systematically characterize samples with the required resolution. A combination of in situ FIB (focused ion beam) lift-out and high-resolution ATEM (analytical transmission electron microscopy) has allowed the characterization of the phase evolution during milling. In particular, boron inclusions, not detected by X-ray diffraction, have been found to remain undissolved in the Fe matrix. © 2009 Taylor and Francis.